Effect of GnRH immunocastration on immune function in male rats - Pan, Fuqiang; Du, Huiting; Tian, Weiguo; Xie, Huihui; Zhang, Bochao; Fu, Wanzhen; Li, Yunsheng; Ling, Yinghui; Zhang, Yunhai; Fang, Fugui; Liu, Ya (Frontiers in Immunology, 2023)
The present study aimed to reveal the effects of immunocastration on the development of the immune system in rats. Seventy rats were randomly assigned into two groups: Control (n = 35) and immunized (n = 35). Twenty-day-old rats were immunized with gonadotropin-releasing hormone (GnRH) and booster immunization was administered every two weeks (three immunizations in total). From 20-day-old rats, we collected samples every two weeks, including five immunized rats and five control rats (seven collections in total). We collected blood samples, testicles, thymuses, and spleens. The results showed that GnRH immunization increased the GnRH antibody titers and reduced the testosterone concentration (both P < 0.05). Compared with the control group, the number of CD4+CD8− cells, CD4−CD8+ cells, and CD4+CD8+ cells increased (P < 0.05) whereas the number of CD4-CD8- cells and CD4+CD25+ cells reduced in the immunized group (P < 0.05) over time. GnRH immunization also increased the relative weights of thymus and spleen (P < 0.05), serum concentrations of interleukin (IL)-2, IL-4, IL-6, IL-10, IL-17 and Interferon-γ (IFN-γ) over time (P < 0.05), and changed the mRNA levels of IL-2, IL-4, IL-6. IL-10, IL-17, IFN-γ, CD4, D8, CD19 GnRH, and GnRH receptor (GnRH-R) in thymus and spleen. Thus, GnRH immunization enhanced the immune markers in thymus, spleen, and blood immune cytokines in rats.